2020
DOI: 10.1186/s12984-020-00744-9
|View full text |Cite
|
Sign up to set email alerts
|

Cortical priming strategies for gait training after stroke: a controlled, stratified trial

Abstract: Background: Stroke survivors experience chronic gait impairments, so rehabilitation has focused on restoring ambulatory capacity. High-intensity speed-based treadmill training (HISTT) is one form of walking rehabilitation that can improve walking, but its effectiveness has not been thoroughly investigated. Additionally, cortical priming with transcranial direct current stimulation (tDCS) and movement may enhance HISTT-induced improvements in walking, but there have been no systematic investigations. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 64 publications
(103 reference statements)
1
45
0
Order By: Relevance
“…Additionally, a single bout of HIIT combined with motor practice could increase skill retention, suggesting a potential impact of HIIT to accelerate motor learning in individuals with stroke [141]. Moreover, priming HIIT through transcranial direct current stimulation enriched with a paretic ankle skill acquisition task could reduce poststroke cortical excitability asymmetry, known to be associated with less functional impairments [142][143][144][145][146], which is not observed when HIIT is performed alone [141] (Table 3). Both HIIT ➚ FNDC5 and Cyt C in the contralesional cortex ➚ indicate an increase; ➘ indicate a decrease; BDNF: brain-derived neurotrophic factor; proBDNF: precursor brain-derived neurotrophic factor; mBDNF: mature brain-derived neurotrophic factor; VEGF: vascular endothelial growth factor; IGF-1: insulin-like growth factor 1; NKCC1: Na + -K + -2Cl − cotransporter; KCC2: K + -Cl − cotransporter; HRR: heart rate reserve; HI: high-intensity; LI; low-intensity; HIIT: high-intensity interval training; MICT: moderate-intensity ➚ Serum BDNF after HIIT ➚ Dendritic growth with patient serum after HIIT ➚ indicate an increase; ⟺ indicate a maintenance; BDNF: brain-derived neurotrophic factor; VEGF: vascular endothelial growth factor; IGF-1: insulin-like growth factor 1; HRR: heart rate reserve; HI: high-intensity; LI; low-intensity; HIIT: high-intensity interval training; MICT: moderate-intensity.…”
Section: Perspectives 61 Is the Combination Between Hiit And Cognitmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a single bout of HIIT combined with motor practice could increase skill retention, suggesting a potential impact of HIIT to accelerate motor learning in individuals with stroke [141]. Moreover, priming HIIT through transcranial direct current stimulation enriched with a paretic ankle skill acquisition task could reduce poststroke cortical excitability asymmetry, known to be associated with less functional impairments [142][143][144][145][146], which is not observed when HIIT is performed alone [141] (Table 3). Both HIIT ➚ FNDC5 and Cyt C in the contralesional cortex ➚ indicate an increase; ➘ indicate a decrease; BDNF: brain-derived neurotrophic factor; proBDNF: precursor brain-derived neurotrophic factor; mBDNF: mature brain-derived neurotrophic factor; VEGF: vascular endothelial growth factor; IGF-1: insulin-like growth factor 1; NKCC1: Na + -K + -2Cl − cotransporter; KCC2: K + -Cl − cotransporter; HRR: heart rate reserve; HI: high-intensity; LI; low-intensity; HIIT: high-intensity interval training; MICT: moderate-intensity ➚ Serum BDNF after HIIT ➚ Dendritic growth with patient serum after HIIT ➚ indicate an increase; ⟺ indicate a maintenance; BDNF: brain-derived neurotrophic factor; VEGF: vascular endothelial growth factor; IGF-1: insulin-like growth factor 1; HRR: heart rate reserve; HI: high-intensity; LI; low-intensity; HIIT: high-intensity interval training; MICT: moderate-intensity.…”
Section: Perspectives 61 Is the Combination Between Hiit And Cognitmentioning
confidence: 99%
“…Additionally, a single bout of HIIT combined with motor practice could increase skill retention, suggesting a potential impact of HIIT to accelerate motor learning in individuals with stroke [ 141 ]. Moreover, priming HIIT through transcranial direct current stimulation enriched with a paretic ankle skill acquisition task could reduce poststroke cortical excitability asymmetry, known to be associated with less functional impairments [ 142 , 143 , 144 , 145 146 ], which is not observed when HIIT is performed alone [ 141 ] ( Table 3 ).…”
Section: Perspectivesmentioning
confidence: 99%
“…Participants in some tDCS trials are being classified as up-or down-regulators depending on their response to anodal tDCS. This classification has been shown to explain some of the changes seen in tDCS and stroke rehabilitation studies (Madhavan et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…After 4 weeks of HISTT both comfortable and maximal walking speeds increased and remained elevated 3 months later ( 17 ). We expected to also detect improvements in spatiotemporal symmetry that were related to these improvements in walking speed because some studies have shown simultaneous improvements in speed and symmetry (although direct relations were not tested) in response to a variety of moderate-intensity walking training interventions ( 29 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The training protocol has been described in detail previously ( 17 , 26 ). Briefly, participants were assigned to one of four parallel groups receiving 15 min of transcranial direct current stimulation (tDCS; stimulation-based priming), ankle motor tracking (AMT; movement-based priming), tDCS and AMT, or rest immediately prior to HISTT described below.…”
Section: Methodsmentioning
confidence: 99%